Retinal effects of Sildenafil in diabetic patients - Bahir, Abdul-Razzak (Journal of the Faculty of Medicine Baghdad, 2008)
Background Sildenafil has been used in the treatment of erectile dysfunction (ED). However it has the disadvantage of many visual disturbances. The aim of this work is to study the effect of sildenafil on diabetic patients which might have ocular problems due to diabetes mellitus. Materials and Methods: A total of 30 subjects were enrolled in the study, they were divided into two groups. The control group consisted of 10 healthy subjects but complaining of ED only and the other (20 patients) had diabetes mellitus and ED as well. All subjects had ocular tests done before and after sildenafil intake. It was obvious that sildenafil changed visual tests from totally normal for controls, before treatent, to visual abnormality in some of the tests after treatment, such as in colour Fac Med Baghdad sense , diplopia & intra ocular pressure ( IOP ). Results: While certain percentage of diabetic patients had visual disturbances even before sildenafil intake. The abnormalities were in visual acuity, visual field and, in fundus appearance. Post – treatment led to increase the percentage of patients with already existing ocular problems and extend them to include some other new ones like change in colour sense , diplopia and increased ( IOP ). Conclusions: Comparing the patient group with the control , pre – treatment tests revealed that diabetic patients had already pre – existing ocular problems due to diabetes such as in the visual acuity , visual field which were statistically not significant ( p>0.05). The only significant (p<0.05) difference was in the fundus appearance. Post – treatment results indicated more ocular damage in diabetic patients as all tests were abnormal compared to control subjects. So, although not significant but ocular complications do exist and might cause unpredictable eye damage to certain percentage of patients which should be taken into consideration.